Peran manajemen sumber daya manusia pada lembaga pendidikan - Chandra Sagul Haratua; Euis Syauqiyah Rahmah; Anita Samirah (Lancar Media Komunikasi, 2023)
Human resource management plays an important role in everyorganization. Similarly in education, the existence of human resource management plays an important role in managingindividuals within the educational framework by performing several stages of the human resource management function, namely plan, organize, direct, and control (POAC) to meet expectations. and target. organization. An organization without human resource management will not perform well due to its very important role in personal development training aimed at improving the quality of the teaching staff needed to adhere to predetermined plans and achieve organizational goals that thecommunity will feel the impact of. Keywords: Human Resource Management; Education